Polglasnik v slovenskem spontanem govoru prebivalcev Obale - Volk, Jana (Jezik in slovstvo, 2018)
The article presents the results of an instrumental analysis of scwa in the spontaneous speech of speakers from the Slovenian coast. The measurements of schwa in spontaneous speech were compared to the measurements of the vowel system of Slovenian and Italian languages (since they are georaphically the closest measurements) obtained in regions across the Italian border. Finally, they were compared to the measurements of the vowel system of standard Slovene. The results of the perceptive analyses of the vowel system of coastal speech indicate that the predicted schwa in the speech of coastal speakers is not realised the same way in all categories, and can even vary in the same speaker. A separate analysis was therefore undertaken for the pronunciations of individual speakers and pronunciations in the context of frequency categories of schwa according to the Slovenian Normative Guide, Slovenian Grammar, and standard Slovenian pronunciation.
Keywords: instrumentalne analize; italijanščina; Obala; polglasnik; slovenščina; spontani govor; sredinski glasovi